PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2018-2021) - Sulastri, Anis; Pamungkas, Imang Dapit (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This research aims to understand corporate governance's impact on financial distress with moderate profitability as a variable. The sample in this study is a property and real estate sector companies listed on the BEI in the 2018-2021 period. The data used in the research consists of secondary data of financial statements and annual reports. Data and hypothetical analysis tools are used with an 8.0 warppls program. The results showed that the board of commissioners, board of directors, does not affect financial distress, the auditing committee does not affect financial distress, and profitability is able to moderate the board of commissioners on financial distress. Nevertheless, profitability has been unable to modernize the board of directors and audit committees on financial distress